Contracts, Phillips Curve and Monetary Policy - Jiménez, Félix (2015)
This paper shows how to obtain a short run aggregate supply curve when there are explicit orimplicit contracts. In the same way it is possible to obtain an expectation augmented Phillips curve. Then, a monetary policy is incorporated to the short run aggregate supply curve or to the Phillips curve in order to model the Central Bank reaction when the actual inflation deviates from the target inflation. Then a model with a Central Bank welfare lost function is developed in order to obtain an optimal monetary policy rule which modifies the synthetic version of the Taylor Rule. This model allows making short run comparative static analyses.